Use of local Hydromacrophytes as phytoremediation agent in pond to improve irrigation water quality evaluated by Diatom Biotic Indices - CATUR RETNANINGDYAH; ENDANG ENDANG ARISOESILANINGSIH; SETIJONO SAMINO (Biodiversitas Journal of Biological Diversity, 2017)
Retnaningdyah C, Arisoesilaningsih E, Samino S. 2017. Use of local Hydromacrophytes as phytoremediation agent in pond to improve irrigation water quality evaluated by Diatom Biotic Indices. Biodiversitas 18: 1596-1602. Irrigation water in Indonesia generally has been polluted because of agricultural, industrial and domestic activity. The aims of this research were to determine the effectiveness of phytoremediation models conducted by planting some local Hydromacrophytes in three phytoremediation ponds through a continuous culture system with water discharge about 0.3 L/seconds for improving the irrigation water quality. The quasiexperimental research was conducted in a phytoremediation pond located in Kepanjen District of Malang, East Java Indonesia. The phytoremediation pond was divided into four interconnected sections. Pond 1 and 2 were planted with some of floating leaf and emergent hydromacrophyte, pond 3 was planted by combinations of same plants added with submerged Hydromacrophytes, while pond 4 was container pond to collecting the water as a result of phytoremediation process. The success of phytoremediation process was known from some physico-chemical parameters of water and some of diatom biotic indices (trophic diatom index/TDI, percentage of pollution tolerant value (%PTV), and Shannon Wiener diversity Index) that was found from artificial substrate been installed in the early treatment. The water quality monitoring performed in each part of the ponds after the plants grew steadily. The results showed that planting of Hydromacrophytes can significantly improve the physico-chemical quality of water. This was reflected in the decline value of conductivity (from 188 Î¼S/cm to 182 Î¼S/cm), turbidity (30 NTU become 8 NTU), total suspended solid (TSS) from 31.3 mg/L to be 5.5 mg/L, nitrates (7.5 mg/L to 3.3 mg/L) and dissolved phosphates (from 0.16 mg./L become 0.04 mg/L) and increasing value of dissolved oxygen (DO) in waters from 2.6 mg/L become 2.9 mg/L. Based on biotic indices there were improvement of the water quality from heavily polluted (diversity index 0.91) become moderately polluted (diversity index 2.07), eutrophic (TDI 52) become mesoeutrophic (TDI 38), and from heavily organic pollution (PTV 93%) to be some organic pollution contribute to eutrophication (PTV 38%). Improvement of water quality was effectively occur after passing through the third pond.